DEVELOPMENT OF MOTORIZED OIL PALM FRUIT ROTARY DIGESTER (Nigerian Journal of Technology, 2013)
A motorized oil palm fruit rotary digester comprising of a feed hopper, hammers, axle, screening plate, v-belt, 2hp electric motor, digesting chamber and frame was designed and developed using standard and locally sourced materials. The performance test analysis showed that its throughput capacity is 117.93kg/hr with a performance efficiency of 64.88% at an optimum operational speed of 621.4rpm. Rate of digestion increased with the mass of the digesting palm fruit while the efficiency of the oil palm fruit digesting machine decreased with increase in mass of the digesting palm fruit in some cases.